Tyrosinase Inhibitory Effect and Antioxidative Activities of Fermented and Ethanol Extracts of Rhodiola rosea and Lonicera japonica - Yuh-Shuen Chen; Hua-Chian Liou; Chin-Feng Chan (The Scientific World Journal)
This is the first study to investigate the biological activities of fermented extracts of Rhodiola rosea L. (Crassulaceae) and Lonicera japonica Thunb. (Caprifoliaceae). Alcaligenes piechaudii CC-ESB2 fermented and ethanol extracts of Rhodiola rosea and Lonicera japonica were prepared and the antioxidative activities of different concentrations of samples were evaluated using in vitro antioxidative assays. Tyrosinase inhibition was determined by using the dopachrome method with L-DOPA as substrate. The results demonstrated that inhibitory effects (ED50 values) on mushroom tyrosinase of fermented Rhodiola rosea, fermented Lonicera japonica, ethanol extract of Lonicera japonica, and ethanol extract of Rhodiola rosea were 0.78, 4.07, 6.93, and >10 mg/ml, respectively. The DPPH scavenging effects of fermented Rhodiola rosea (ED50 = 0.073 mg/ml) and fermented Lonicera japonica (ED50 = 0.207 mg/ml) were stronger than effects of their respective ethanol extracts. Furthermore, the scavenging effect increases with the presence of high content of total phenol. However, the superoxide scavenging effects of fermented Rhodiola rosea was less than effects of fermented Lonicera japonica. The results indicated that fermentation of Rhodiola rosea and Lonicera japonica can be considered as an effective biochemical process for application in food, drug, and cosmetics.